Madrasah Head's Strategy in Increasing the Effectiveness of Extracurricular Activities At Mts Zia Salsabila - Wardani*, Wardani; Mesiono, Mesiono (Riwayat: Educational Journal of History and Humanities, 2024)
Mts Zia Salsabila is a private junior high school that has accreditation B. The madrasa head's strategy in increasing the effectiveness of extracurricular activities is quite good, but in implementing extracurricular activities there are still problems in increasing the effectiveness of extracurricular activities. The aim of this research was to determine the steps taken by the head of the madrasah in increasing extracurricular activities at MTS Zia Salsabila, as well as the inhibiting and supporting factors for the head of the madrasah in increasing extracurricular activities at MTS Zia Salsabila. This research uses qualitative methods using interview, observation and documentation techniques, the results obtained and it can be concluded that the steps taken by the head of the madrasah in increasing extracurricular activities are in the form of providing teachers, extracurricular activities run because they have a role model teacher, then the head of the madrasah provides a place training location, and the head of the madrasah facilitates students who want to take part in the competition, while the supporting factors for the head of the madrasah in increasing extracurricular activities are the spirit of support from teachers to carry out extracurricular activities, as well as support from the students' parents, as well as the inhibiting factor being the lack of adequate infrastructure inadequate.